PENERAPAN METODE GUIDED NOTE TAKING (GNT) PADA MATERI LINGKARAN SISWA SMP - Petrus Kanisius Sare; Sofia Sa'o; Gregorius Taga (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This research aims to improve the Mathematics learning process for class VIIA students at SMP Negeri 4 Wolowaru and to determine the improvement in student learning outcomes using the Guided Note Taking (GNT) method for class VIIA students at SMP Negeri 4 Wolowaru. This type of research is Classroom Action Research (PTK) with a qualitative approach. This research was carried out at SMP Negeri 4 Wolowaru class VIIA with a total of 22 students consisting of 13 male students and 9 female students. Data collection techniques are carried out using observation, tests and documentation. Indicators of student success are characterized by increasing student learning outcomes with a KKTP of 65 and student completion reaching 75%. The research results showed that student activity during the learning process took place through the use of the GNT method in cycle I with a percentage of 69.05%, while in cycle II it increased with a percentage of 76.35%. The pre-action test results were 13.64% in cycle I, increasing to 63.63% and increasing in cycle II to 95.45%. Based on the research results, it can be concluded that using the Guided Note Taking method can improve student learning outcomes.